2019
DOI: 10.1021/acs.jpcc.8b10877
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Chemisorption Isotherms on Platinum Particles at Catalytic Temperatures: Langmuir and Two-Dimensional Gas Models Revisited

Abstract: Density functional theory (DFT) and dihydrogen chemisorption uptakes at temperatures relevant to catalysis are used to determine and interpret adsorption enthalpies and entropies over a broad range of chemisorbed hydrogen (H*) coverages (0.1 ML to saturation) on Pt nanoparticles (1.6, 3.0, and 9.1 nm mean diameters) and Pt(111) surfaces. Heats of adsorption decrease by 30 kJ mol −1 as H 2 coverage increases from nearly bare (0.1 ML) to saturated (∼1 ML) surfaces, because of the preferential saturation of lowco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(80 citation statements)
references
References 97 publications
(140 reference statements)
10
70
0
Order By: Relevance
“…The temperature ranges (1050–1250 K) and associated step densities of our experimental (solid box) and Ostwald process (dashed box) conditions are indicated in the plot. The step densities for the Ostwald catalyst are not known, but we consider typical step/edge densities found on catalytic nanoparticles 42 , 43 as representative for real catalysts.…”
Section: Further Analysis and Discussionmentioning
confidence: 99%
“…The temperature ranges (1050–1250 K) and associated step densities of our experimental (solid box) and Ostwald process (dashed box) conditions are indicated in the plot. The step densities for the Ostwald catalyst are not known, but we consider typical step/edge densities found on catalytic nanoparticles 42 , 43 as representative for real catalysts.…”
Section: Further Analysis and Discussionmentioning
confidence: 99%
“…DFT calculations have also shown that the adsorption energy of sulfur on the surface of different fcc metals like Au, Ag, Cu and Pt follows the general trend (100) ≈ (110) > (111) [27] . In addition to the strong covalent and ionic metal‐sulfur bonds, van der Waals dispersive forces provide further possibilities which is especially interesting for S‐carrying ligands by bringing more atoms of a ligand molecule to the gold surface [26a] . In general, attractive or repulsive forces, for example, based on van der Waals forces, hydrogen bonding, or electrostatic interactions between the ligands influence the number of molecules that can be accommodated on the gold nanoparticle surface.…”
Section: Resultsmentioning
confidence: 99%
“…Entropies, vibrational frequencies, and pre-exponential factors for diffusion events may also be obtainable from the PES. 23 The automated collection of all thermodynamic and kinetic data, when interfaced with codes to perform kinetic modeling, can then enable high-throughput screening of both monometallic and alloy clusters for catalysis and materials science In summary, we presented an automated, highly parallelizable approach-the ACSS method-to generate approximate 2D PESs of 3D nanocluster surfaces. These PESs fully characterize the stable adsorption sites and diffusion paths of adsorbates on the surfaces of nanoclusters with minimal human workload.…”
Section: Discussionmentioning
confidence: 99%
“…Because PESs are rich in information, researchers increasingly employ them in catalysisrelated problems. 23,24 Until now however, PESs have mainly been used to study two-dimensional (2D) surfaces such as extended slab models.…”
Section: Introductionmentioning
confidence: 99%